Learning Model of Undergraduate Students: Confirmatory Factor Analysis - Pariyaporn Tungkunanan (My University, 2020)
The research aimed to find the learning model of the undergraduate students by Confirmatory Factor Analysis (CFA).The objective was design learning model.The Methods of this Study process to find the learning model of the undergraduate students is divided into two phrases.The 1st phrase: the preliminary study and the 2nd phrase: Confirmatory Factor Analysis (CFA).The result found that learning model of the undergraduate that support capability of the learners to be qualified graduates and competitive in the international consist of (1) expectation, (2) planning by experience and reflective observation, (3) attention, retention and memory storage, (4) learning method, (5) retrieval by reproduction or making concept by conclusion principles, and (6) motivation or reinforcement.
Keywords: Phrase; Factor (programming language); Education and Critical Thinking Development